Big data Use Of Big Data Analiytical Technology In Analiyzing User Behavior On Social Media: Use Of Big Data Analiytical Technology In Analiyzing User Behavior On Social Media - andre ramadhan srg; achmad ali akbar karo sekali; syahril tio ramadhan; supina batubara (Yayasan Sinergi Multidimensi Kreatif, 2024)
The use of big data analytics technology in analyzing user behavior on social media allows us to identify trends, preferences, and complex behavioral patterns through the analysis of large and diverse data. By leveraging algorithms and predictive models, we can better understand how users interact with social media platforms, providing valuable insights to optimize marketing strategies, improve user experience, and even detect potential reputational issues or risks. Keywords Translated with DeepL.com (free version):